A Review of Language-Sensitive Research in International Business: A Multi-Paradigmatic Reading - Piekkari, Rebecca; Gaibrois, Claudine; Johansson, Marjana (Journal of Comparative International Management, 2022)
This paper reviews language-sensitive research in International Business (IB) by asking how paradigmatic positions affect knowledge production in this field of study. Paradigms refer to the researchers’ assumptions about how research should be conducted and reported. Because they affect the theoretical aim and framing of a study, the data sources, and analysis techniques used, paradigms ultimately shape the kind of knowledge produced. To study how paradigmatic choices influence the knowledge produced, we compared 299 publications in the field of language-sensitive research with 229 publications in mainstream IB by determining the paradigmatic position from which each study had been conducted. Our analysis shows that the paradigmatic diversity of language-sensitive research exceeds that of mainstream IB. Although positivism still dominates language-sensitive research in IB, interpretivist and critical studies have accounted for a growing proportion of research over the years and exceed those in mainstream IB research. We suggest that the norms of the specific research field and of academia in general strongly influence paradigmatic choices, and thus the kind of knowledge researchers produce. The review opens up a novel perspective on knowledge production within language-sensitive IB research.